2021
DOI: 10.3390/ijms22052466
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial Metabolism in Prostate Cancer with Triterpenoids

Abstract: Metabolic reprogramming is a hallmark of malignancy. It implements profound metabolic changes to sustain cancer cell survival and proliferation. Although the Warburg effect is a common feature of metabolic reprogramming, recent studies have revealed that tumor cells also depend on mitochondrial metabolism. Due to the essential role of mitochondria in metabolism and cell survival, targeting mitochondria in cancer cells is an attractive therapeutic strategy. However, the metabolic flexibility of cancer cells may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…The metabolism of healthy prostate epithelial cells and acinar epithelial cells are regulated by glycolysis [293,294]. In normal prostate, pyruvate in cytosol enters the mitochondria to be converted into acetyl-coA.…”
Section: Glycolysismentioning
confidence: 99%
See 3 more Smart Citations
“…The metabolism of healthy prostate epithelial cells and acinar epithelial cells are regulated by glycolysis [293,294]. In normal prostate, pyruvate in cytosol enters the mitochondria to be converted into acetyl-coA.…”
Section: Glycolysismentioning
confidence: 99%
“…Under anaerobic conditions, glycolysis is favored, and very little pyruvate is presented to the aerobic mitochondria [267,294]. Regardless of oxygen availability, PCa cells favor glycolysis [114,267,271,294].…”
Section: Glycolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that cellular metabolic reprogramming occurs during the development of prostate cancer and that triterpenoids can intervene in multiple metabolism pathways of prostate cancer cells. 17 It has been reported that UA alters the glycolysis of breast cancer cells with different phenotypes. 18 However, there are few studies on the metabolic, epigenome,…”
Section: Introductionmentioning
confidence: 99%